Energetics and spatio-temporal variability of semidiurnal internal tides in the Bay of Bengal and Andaman Sea. (November 2020) - Jithin, A.K.; Francis, P.A.; Unnikrishnan, A.S.; Ramakrishna, S.S.V.S.
Abstract: Energetics of semidiurnal barotropic and internal tides in the Bay of Bengal (BoB) and Andaman Sea (AS) are studied using the simulations from a high-resolution ocean general circulation model. Barotropic M 2 tide, which is the largest tidal constituent in this region, loses about 65.5 GW of energy in the BoB and AS. Most of this barotropic energy (46.5 GW) is dissipated by means of bottom friction in the shallow regions, such as the head of the bay and the Gulf of Martaban. Due to the interaction of barotropic tides with bottom topography, about one-third of the barotropic M 2 energy (19.1 GW) gets converted into internal tides and most of this conversion (84%) occurs over the Andaman–Nicobar (AN) Ridge. On the contrary to the estimates in earlier studies, our results show that a large part (59%) of this internal tide energy in the BoB and AS gets dissipated far away from the generation sites. Compared to the BoB, energy dissipation rates are found to be large over the entire AS and it could result in enhanced vertical mixing in this region. Further, analysis of the temporal variability of conversion within the model domain shows that energy conversion in the semidiurnal band varies between 11 to 27 GW over a spring–neap cycle. Seasonal variability in the stratification due to river runoff significantly changes the conversion of tidal energy at the generation sites in the northern BoB and AS. Our study revealed that westward radiating internal tides from AN Ridge undergo path alteration (refraction) due to the time-varying mesoscale circulation and such path alterations cause large intraseasonal variability in internal tide activity and redistribution of internal tide energy available for mixing in the remote areas such as the continental margins of the western BoB. Highlights: Eastern Andaman Sea and head bay are the main areas of frictional tidal dissipation. One-third of M2 tidal energy (19 GW) dissipates by generation of internal tides. About two-third of internal tide energy dissipates away from the generation sites. Seasonal variability in energy conversion is strong in the northern bay. Changes in mesoscale circulation alter the path of internal tide propagation.